Effect of Clustered Nursing Care on Sleep Behaviors of the Preterm Neonates Admitted to the Neonatal Intensive Care Unit - Marjan Bazregari; Jila Mirlashari; hadi ranjbar; Batool Pouraboli (Mashhad University of Medical Sciences, 2019)
Background: Premature neonates admitted to the neonatal intensive care unit (NICU) undergo sleep disorder due to various manipulations. The present study aimed to investigate the effect of clustered nursing care on sleep behaviors in premature neonates admitted to NICUs. Methods: This clinical trial study was conducted on 60 neonates selected through convenience sampling method out of the infants admitted to the NICU. First, in the control group, a constant nurse took care of the neonates in a complete shift. The nurse observed the neonates sleep behaviors every two min for 45 min and recorded them in the questionnaire. The intervention group was investigated one week after the control group. The neonates 'sleep behaviors were observed and recorded every two min by Prechtl instrument. All the data were analyzed by the Mann-Whitney U test using SPSS software version 16. Results: The mean sleep times in the control group were as follow: quiet sleep 5 min and 86 millisecond, active sleep 21 min and 50 milliseconds, quiet wake 4 min and 6 milliseconds,alertness9 min and 6 milliseconds, and cry1 min and 76 millisecond .On the other hand, in the neonates who received clustered care in the intervention group, the mean timings were as follow: quiet sleep time 19 min and 33 millisecond, active sleep 24 min and 66 millisecond, quiet wake 1 min and 76 millisecond,alertness2 min and 76 millisecond, and cry0.13 min. According to the mentioned times, it could be concluded that the neonates in the test group had a quiet and active sleep (P <0.05). Conclusion: Findings of this study demonstrate that cluster care can significantly increase the time of quiet and active sleep in the newborns. Based on the result, it is recommended that this kind of care be provided in the NICU program, as well as in the syllabus of students and nursing retraining.